Police science as an emerging scientific discipline - Nägel, Christof (International journal of police science & management, 2020)
This article examines the epistemological and institutional configuration of police science. Our results indicate that although police science fulfills the epistemological prerequisites for a scientific discipline, the corresponding institutionalization, which is a necessary condition of its consolidation, has taken place only partially and in a few Western countries. Institutional establishment of police science fails primarily because of the lack of a collective definition of the field, but also because of deficits in the density of interorganizational contacts and the flow of information. This has several theoretical, but also practical implications, mainly on the issue of institutional legitimacy, which are discussed at the end of this article.